2018
DOI: 10.1016/j.apcatb.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Connecting structural, optical, and electronic properties and photocatalytic activity of Ag3PO4:Mo complemented by DFT calculations

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 64 publications
5
53
1
2
Order By: Relevance
“…Many studies have shown that reactive oxygen species (ROS), such as hydroxyl radicals (OH * ), singlet oxygen ( 1 O 2 ), and hydroperoxyl radicals (HOO * ), are responsible for the photocatalytic activity of semiconductors, which are photo‐induced by holes and electrons (h and e' , respectively) . According to Rehan et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that reactive oxygen species (ROS), such as hydroxyl radicals (OH * ), singlet oxygen ( 1 O 2 ), and hydroperoxyl radicals (HOO * ), are responsible for the photocatalytic activity of semiconductors, which are photo‐induced by holes and electrons (h and e' , respectively) . According to Rehan et al .…”
Section: Resultsmentioning
confidence: 99%
“…This happens because semiconductors that present an E gap in the near‐ultraviolet region, which are more susceptible to photocorrosion, and causes the active sites of the materials to be covered by the new species produced during the photocatalytic process . In some studies of the group with Ag‐based materials, it was possible to observe the formation of Ag 0 and Ag‐based oxides during the photocatalytic cycles, and that depending on the concentration of these species, at first a slight increase in the photocatalysis, followed later by a decrease in photocatalytic efficiency due to degradation of the Ag‐based material . Since the AgX (X=Cl, Br and I) solubility constant follows the order‐AgCl (1.77×10 −10 ) > AgBr (5.35×10 −12 ) > AgI (8.52×10 −17 )‐AgCl and AgBr are more susceptible to photocorrosion and the loss of efficiency during the photocatalytic cycles being more pronounced for these materials .…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the promise of these materials will need signicantly more detailed studies, e.g. physicochemical (for example ESR), [80][81][82][83] in vitro, 84 in silico, [85][86][87] in vivo (in pre-clinical models, e.g. small mammals), 88 and there-aer clinical trials prior to translation to the clinic; such nanocomposites therefore have a variety of potential technical and medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] In order to overcome these weaknesses and improve its photocatalytic performance, numerous methods were adopted. [ 14,15 ] The efforts mainly included controlling the crystal morphology, [ 16 ] facet engineering, [ 17 ] metal deposition, [ 18 ] ion doping, [ 19 ] or coupling with another semiconductor. [ 20 ] All these attempts demonstrate that the key to solve the problem is to achieve effective spatial separation and rapid transfer of photogenerated charges to the surface reaction sites.…”
Section: Introductionmentioning
confidence: 99%